2020
DOI: 10.1177/1420326x20975468
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the impact of a first-time central heating intervention on resident mental wellbeing

Abstract: Fuel poverty affects around 34% of European homes, representing a considerable burden to society and healthcare systems. This pilot study assesses the impact of an intervention to install a new first time central heating system in order to reduce fuel poverty on household satisfaction with indoor temperatures/environment, ability to pay bills and mental well-being. In Cornwall, 183 households received the intervention and a further 374 went onto a waiting list control. A post-intervention postal questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Living circumstances, such as dissatisfaction with housing (LC1) and experiencing fuel poverty (LC3), were only found to be associated with poorer mental wellbeing among residents of privately owned and rented properties [ 45 ]. Those who were privately renting and reported problems with neighbourhood conditions, such as homelessness (NC32) and dogs in the area (NC39), or who felt the local sport and leisure facilities needed improving (NC22), reported poorer mental wellbeing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Living circumstances, such as dissatisfaction with housing (LC1) and experiencing fuel poverty (LC3), were only found to be associated with poorer mental wellbeing among residents of privately owned and rented properties [ 45 ]. Those who were privately renting and reported problems with neighbourhood conditions, such as homelessness (NC32) and dogs in the area (NC39), or who felt the local sport and leisure facilities needed improving (NC22), reported poorer mental wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…As with previous studies, living circumstances were found to be associated with mental wellbeing in the present study [ 11 , 17 , 46 , 47 ]. However, while fuel poverty and housing conditions are recognised as significant determinants of health, their impact on mental wellbeing was found to be limited to residents of privately owned and rented properties [ 45 ]. It is possible that private rental landlords may be less likely to invest in the property [ 28 , 48 ], which may explain this differential impact on wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is recognised that it is very difficult to design a truly comparable group of participants to act as a comparator in such small-scale evaluations [ 32 ]. It is suggested that future studies consider a stepped intervention design with a “waiting list control group” [ 33 ]. Nonetheless, the current evaluation compared outcomes for beneficiaries of different types of intervention and conducted a qualitative investigation to explore beneficiaries’ experiences of how the programme has impacted on their health and wellbeing; initial literature searches suggest a need for further research on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The impact is felt in the additional costs associated with cooling and heating, as well as through a knock on effect on overall budgets for other needs such as food (De Vries & Blane, 2013; Gouveia et al, 2019; Nord & Kantor, 2006; Thomson et al, 2019). The condition of the housing stock in the place in question is also important: levels of insulation and state of repair of housing have a direct effect on levels of energy poverty, as well as the associated impacts (Peralta et al, 2017; Poortinga et al, 2017; Sharpe et al, 2020; Tonn et al, 2021). The presence or absence of heating and cooling infrastructures in particular places also shapes energy poverty, with some nations having limited access to central heating or cooling technologies (Gómez‐Navarro et al, 2021).…”
Section: Broader Conditions That Shape Vulnerability To Energy Povertymentioning
confidence: 99%